The Effect of Entrepreneurship Education, Entrepreneurial Motivation, and the Need for Achievement on Entrepreneurial Intentions Through Self-Efficacy - Widyaningrum, Bakti; Nursafaat, Firman; Afriza, Edi Fitriana (Journal of Educational Analytics, 2024)
This study aims to determine the influence of entrepreneurship education, entrepreneurial motivation, and the need for achievement on entrepreneurial inteThis study aims to determine the influence of entrepreneurship education, entrepreneurial motivation, and the need for achievement on entrepreneurial intentions through self-efficacy. This research uses a quantitative approach with a survey method. The place of implementation of this research is at SMK Islamiyah Tasikmalaya. Sampling technique with saturated samples of as many as 182. Data analysis using path analysis. The results show: that entrepreneurship education affects efficacy; entrepreneurial motivation affects self-efficacy; the need for achievement affects self-efficacy; entrepreneurship education does not affect entrepreneurial intentions; Entrepreneurial motivation does not affect entrepreneurial intentions; the need for achievement does not affect entrepreneurial intentions; self-efficacy has a positive effect on entrepreneurial intentions;  entrepreneurship education influences entrepreneurial intentions through efficacy; Entrepreneurial motivation affects entrepreneurial intentions through self-efficacy; and the need for achievement affects entrepreneurial intentions through efficacy.